Tympanic Membrane Rupture During Stereotaxic Surgery Disturbs the Normal Feeding Behavior in Rats - Barahona, María J; Rojas, Joaquín; Uribe, Elena A; García-Robles, María A (Frontiers in Behavioral Neuroscience, 2020)
Stereotactic surgery is a widely used procedure in neuroscience research to study the brain´s regulation of feeding behavior. In line with this notion, this study aims to assess how food consumption and feeding patterns are affected in response to the use of auditory bars that preserve or damage the tympanic membrane during stereotactic surgery. Our previous observations led us to hypothesize that the traumatic tympanic membrane rupture affects food intake and feeding patterns in rats undergoing stereotactic procedures. Thereby, female and male rats were cannulated in the third ventricle (3V) using both types of auditory bars. Post-surgical pain was assessed using the grimace scale. Food intake, meal patterns and weight gain or loss were analyzed for 5-7 consecutive days after surgery. Normal food intake, increased body weight and regular meal patterns were observed from postoperative day 2 when the stereotactic procedure was performed using auditory bars that maintain the integrity of the tympanic membrane. However, tympanic membrane rupture prevented the expected recovery of food intake and body weight. This effect was accompanied by an alteration in eating patterns, which was persistent over 7 days of recovery. Thus, tympanic membrane preservation during surgery is necessary to evaluate short-term feeding patterns. This study demonstrates auditory bars that do not damage the tympanic membrane should be used when performing stereotactic surgery for subsequent analysis of rat behavior.